Voltage Stability Investigation of the Egyptian Grid with High Penetration Level of Wind Energy - S. K. El-Goharey, Hamdy; A. Omran, Walid; T. M. Taha, Adel; M. El- Samanoudy, Salwa (Recent Advances in Communications and Networking Technology, 2015)
There has been a rapid increase in wind turbine connection to distribution and transmission networks in recent years. With individual wind turbines approaching the multi - MW and the wind plants, as a result, approaching the output rating of conventional power plants, a deeper understanding of their potential impacts on interactions with the bulk electric power system is needed. The increased penetration makes the power network more dependent on, and susceptible to, the wind energy production. As the wind power penetration into the grid increases rapidly, the influence of wind turbines on the power quality and voltage stability is becoming more important. The main objective of this study is to analyze the voltage stability of the Egyptian Electrical Network with large scale wind power under normal operation and under single contingency (N-1). The single contingency is defined as the loss of any transmission line, transformer, or generator. In addition, the paper determines the size of reactive power compensation devices (capacitors or STATCOM) that should be installed at weak buses to prevent the voltage collapse.
Keywords: voltage sensitivity